1996
DOI: 10.4319/lo.1996.41.7.1425
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration, recycling, and trophic transfer of trace metals by microbial food‐web organisms in the pelagic surface waters of Lake Erie

Abstract: Rapid regeneration of 'OgCd and 65Zn from their picoplankton prey into the dissolved phase by microzooplankton was observed in water sampled from the pelagic surface waters of Lake Erie (summer 1994 and 1995). Trace metals were added to grazing (lake water < 2'10 brn) and control (lake water CO.2 pm) treatments in the form of radiolabeled Synechococcus, Picoplankton (0.2-3 pm) were grazed heavily by consumers in the nanoplankton (3-20 pm) and microplankton (20-2 10 pm) size classes (collectively referred to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 31 publications
4
21
0
Order By: Relevance
“…Biologically-mediated regeneration is critical to metal cycling in marine and freshwater systems (Hutchins et al 1993, Hutchins & Bruland 1994, Twiss & Campbell 1995, Twiss et al 1996, Wang & Fisher 1998b. The present results have demonstrated that the physiological turnover of assimilated trace metals in Calanus sinicus is relatively independent of algal diet or the amount of food ingested, similar to the results of previous studies on other copepods .…”
Section: Regeneration Of Trace Metalssupporting
confidence: 80%
“…Biologically-mediated regeneration is critical to metal cycling in marine and freshwater systems (Hutchins et al 1993, Hutchins & Bruland 1994, Twiss & Campbell 1995, Twiss et al 1996, Wang & Fisher 1998b. The present results have demonstrated that the physiological turnover of assimilated trace metals in Calanus sinicus is relatively independent of algal diet or the amount of food ingested, similar to the results of previous studies on other copepods .…”
Section: Regeneration Of Trace Metalssupporting
confidence: 80%
“…These are the biologically important elements such as Mn, Co and Mo, and also Cd. The latter is known to substitute Zn in the carbonic anhydrase of diatoms in case of Zn limitation conditions (Lane et al, 2005) and both are significantly affected by the trophic transfer along the foodwebs (Twiss et al, 1996). Peak concentrations of these elements occurred during the second night of monitoring.…”
Section: Element Concentration Variation During the Diurnal Photosyntmentioning
confidence: 99%
“…The release rates of metals from decomposing fecal material have been quantified for a variety of conditions and can affect the rates of metal remineralization during their descent in the water column (Lee andFisher 1992, 1994;Reinfelder et al 1993;Wang et al 19966). Regeneration of assimilated trace elements by zooplankton grazing can significantly affect their geochemical cycling and residence times and can affect their bioavailability to phytoplankton (Hutchins and Bruland 1994;Lee and Fisher 1994;Twiss and Campbell 1995;Twiss et al 1996;Wang et al 19966). However, mechanistic and quantitative studies of zooplankton regeneration have been limited.…”
mentioning
confidence: 99%